Institution transfers, the Marshall Plan, Europe, and Ukraine: An analytical narrativ - Atin Basuchoudhary; Andreas Freytag; Troy Siemers (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
This paper offers an analytical narrative based on an assurance game with two separate populations in an evolutionary setting. In our model, Donors and Recipients are two populations; let us call them Europe and Ukraine. The donor population has two types. A proportion of this population wants to promote a Marshall Plan-type model for the recipient state, and another prefers isolationism. A proportion of the population of the recipient state also intends to coordinate a Marshall Plan-type economic integration. In contrast, others prefer foreign aid but view further integration as a violation of sovereignty (or, with Ukraine, may be afraid of further Russian attacks from this integration). Marshall plan type coordination provides the highest payoffs through, e.g., the peace dividend, better institutions in Ukraine, widened European integration trade links, or global financial integration. Coordination is costly because it requires substantial institutional change on both sides. We use simulations to track outcomes given that European support for Ukraine and Ukrainian desire for aid may be endogenous. Further, we show how these endogenous outcomes respond to political shocks in Europe that affect European support for Ukraine and implicitly the lack of support for Ukraine.
Keywords: P41; C73; 330; Institutional Transfer; Institutional Coordination; Evolutionary Game Theory; Ukraine War; Foreign Aid